Perfil socioeconômico da pesca artesanal no semiárido potiguar, Brasil - Silva, Francisco das Chagas Nogueira Bezerra (Universidade Federal Rural do Semi-Árido, 2021)
The main objective of the work was to draw the socioeconomic profile of artisanal fishing in the municipality of Apodi located in the semi-arid Potyguar region in the western region of the Rio Grande do Norte. Data obtained during the annual re-registration carried out in colony z-48 in the municipality of Apodi in 2021 in the period June to August were used. Fishing is the main economic activity of families and has a subsistence character. Despite the fact that most of them practice activities other than fishing, having a low level of education causes difficulties in accessing school. The fishing activity is developed in a family economy, partnership and individually, being employed in the production of family labor and these dedicate an average of 4 hours of daily work to fishing, facilitating parallel activities such as agriculture and livestock. The vast majority of professionals are registered at the fishermen's colony, having access to unemployment insurance to fishermen during the period when activities are stopped and always participate in the meetings. Fishing vessels are characterized by mostly canoes and rowboats; it was found that fishermen do not use any type of safety equipment such as life jackets, buoys and fire extinguishers, however insufficient. In the Santa Cruz Dam, Apodi Lagoon and in other reservoirs, fishermen reported using fishing techniques using the following fishing materials, line and hook, holding net, cast net and trap, in this case the pot for shrimp fishing candy. Fishing in the region is characterized by the great diversity of species caught, including Nile Tilapia, Tucunaré, Curimatã, Hake, Traíra, Piaba, and Shrimp. Part of the production is transferred to middlemen who sell the fish to local businesses and other cities, another part is sold directly by the fisherman at the open market and another part is for consumption. The fish farming activity is present in the region with production in cages in the Dam and production in excavated tanks in various regions of the city, representing several opportunities for family and local economic development. One of the main problems faced by fishermen is commercialization, it can be considered that there is no structured way to do it and the acquisition is left to the middlemen, in addition to the existing conflicts between the fishermen themselves and the lack of oversight public bodies, in addition to the lack of effective public policies for the class.
Keywords: Colônia de pescadores; Comércio local; Desenvolvimento econômico; Seguro defeso; Lagoa do Apodi; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA